Program Siaga Cegah Hipertensi dan Stroke pada Masyarakat di Wilayah Tamalanrea Makassar - Arafat, Rosyidah; Setyawati, Andina; Ningrat, Syahrul (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
As an effort to address hypertension, which poses a risk of stroke, the Makassar City Government has launched the Sijagai program, a health program in the Makassar City Health Center (Puskesmas). Health workers from the Community Health Center (Puskesmas) visit residents' homes to conduct health checks and treat them. This community service program focuses on three activities: healthy exercise for the elderly, risk factor detection through blood pressure (BP), blood glucose (GDS), and total cholesterol screening, and education on hypertension prevention and management, a low-salt diet, and early stroke detection. Evaluation results show that more than 50% of patients with hypertension and high cholesterol experienced improved knowledge and skills after the education, as evidenced by their ability to repeat information and role-play.